Carbon Concentration in Algae: Reducing CO2 From Exhaust Gas. Issue 9 (September 2017) - Ghosh, Atreyee; Kiran, Bala
Abstract : Algal carbon-concentrating mechanisms can be used to sequester CO2 from the atmosphere, and the resulting biomass can produce various value-added products. Mechanisms for carbon concentration in algae are complex and sometimes inefficient. We need to understand how algae successfully overcome these challenges while capturing CO2 from their nearby environment.